2009
DOI: 10.1371/journal.pone.0006232
|View full text |Cite
|
Sign up to set email alerts
|

Use of an EZ-Tn5-Based Random Mutagenesis System to Identify a Novel Toxin Regulatory Locus in Clostridium perfringens Strain 13

Abstract: BackgroundAlthough useful for probing bacterial pathogenesis and physiology, current random mutagenesis systems suffer limitations for studying the toxin-producing bacterium Clostridium perfringens.Methodology/Principal FindingsAn EZ-Tn5-based random mutagenesis approach was developed for use in C. perfringens. This mutagenesis system identified a new regulatory locus controlling toxin production by strain 13, a C. perfringens type A strain. The novel locus, encoding proteins with homology to the AgrB and AgrD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(142 citation statements)
references
References 46 publications
7
135
0
Order By: Relevance
“…perfringens carries a chromosomal operon with partial homology to the S. aureus operon encoding components of the Agr quorum-sensing (QS) system. This agr-like operon was shown to regulate CPA and PFO production by C. perfringens type A strain 13, presumably by encoding components of a similar QS system (155,156). It also controls the production of several plasmid-encoded C. perfringens toxins, including CPB2 and CPE expression in type A strain F5603 (157), CPB production in type C strain CN3685 (158) and type B strains CN1793 and CN1795 (159), and ETX production in type D strain CN3718 (154).…”
Section: The Agr-like Regulatory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…perfringens carries a chromosomal operon with partial homology to the S. aureus operon encoding components of the Agr quorum-sensing (QS) system. This agr-like operon was shown to regulate CPA and PFO production by C. perfringens type A strain 13, presumably by encoding components of a similar QS system (155,156). It also controls the production of several plasmid-encoded C. perfringens toxins, including CPB2 and CPE expression in type A strain F5603 (157), CPB production in type C strain CN3685 (158) and type B strains CN1793 and CN1795 (159), and ETX production in type D strain CN3718 (154).…”
Section: The Agr-like Regulatory Systemmentioning
confidence: 99%
“…Since the highly conserved agr-like operon present among most or all C. perfringens strains apparently does not encode the AgrA/ AgrC two-component system of the S. aureus Agr QS operon (155,156), it was proposed that C. perfringens uses the VirS/VirR system for responding to Agr-like regulatory system signaling (155). While this putative relationship may yet explain the regulation of some toxins by some C. perfringens strains, recent results indicated that Agr-like regulatory system signaling in this bacterium does not always require the VirS/VirR system (154).…”
Section: The Agr-like Regulatory Systemmentioning
confidence: 99%
“…The banding pattern indicated that each of the mutants had an insertion in a different location and only 2 (ϳ12%) of the clones had multiple insertions (data not shown). These are higher rates of multiple insertions than those reported for the Mu transposition system (0 out of 30 tested [6]) and the EZ-Tn5-based system (0 out of 8 tested [7]), but this rate may be lowered by changing the level of induction of the transposase gene. The chromosomal DNA flanking the site of insertion in 10 of these clones was sequenced (see Materials and Methods); the sites of insertion were randomly distributed around the chromosome, and none of the insertions were in rRNA operons (see Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 53%
“…A more efficient EZ-Tn5-based random mutagenesis system showed a lower but significant frequency of insertion into rRNA genes (18%) in comparison to the phage Mu-based system (7). Another major limitation of the EZ-Tn5 and phage Mu systems is that both require that the recipient strain be highly transformable by electroporation (6,7).…”
mentioning
confidence: 99%
“…While the LuxS quorum sensing system does not seem to be important for host cell-induced upregulation of toxin production, two studies recently showed that inactivating the agrB gene in C. perfringens type A strain 13 delays the onset of α-toxin and PFO production when this strain grows in bacterial media. 17,18 Those findings open the possibility that the Agr quorum sensing system might also be involved in host-cell induced toxin upregulation by type C isolates.…”
Section: Questions For Future Researchmentioning
confidence: 93%